Tinjauan Fiqh Jinayah terhadap Pencemaran Nama Baik - Fathullah (Asy-Syari’ah : Jurnal Hukum Islam, 2020)
Reality shows that there is an act of arrest which causes defamation of someone carried out by the authorities. So it should be examined in the form of a thesis with the title: “Jinayah Fiqh Review of Defamation”. In an effort to answer the problem in this study, the author uses library research, namely by conducting research on library materials, then an analysis is related to the problem under study. The study was conducted using a normative juridical approach. Normative legal research is legal research carried out by examining mere secondary literature or data. The research results show that the act of defamation or defamation of people has the same meaning as the act of defamation as regulated in Article 130 of the Criminal Code. Of course defamation is an act that violates the law, both verbally and in writing. which attacks someone’s honor which results in damage to one’s reputation or reputation, by spreading news that is not in accordance with the facts, and spreading the news to the general public which could cause harm to the parties concerned. Finally, Fiqh Jinayah considers that criminal acts of Defamation are prohibited and included in the category of ta’zir (determined by the judge as the bearer of legitimacy in the field of sentencing).